Synthesis and characterization of flurbiprofen hydrazide derivatives as potential anti-HCV, anticancer and antimicrobial agents - TATAR, ESRA; KÜÇÜKGÜZEL, İLKAY; SÜZGÜN, PELİN; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (SPRINGER BIRKHAUSER, 2013)
A novel series of new flurbiprofen hydrazide derivatives 2-(2-fluorobiphenyl-4-yl)-N'-[(substituted phenyl/5-nitro-2-furyl)methylene]propanehydrazide (3a-k), 2-(2-fluorobiphenyl-4-yl)-N-(2-substituted-4-oxo-1,3-thiazolidine-3-yl)propanamide (4a-b, 4d-k), 2-[2-(2-fluorobiphenyl-4-yl) propanoyl]-N-substituted hydrazinecarbothioamide (5a-h) and 2-(2-fluorobiphenyl-4-yl)-N'-[(3-methyl-4-oxo-1,3-thiazolidin-2-ylidene]propanehydrazide (6a-b, 6e and 6g) has been synthesized in this study. All synthesized compounds were screened for antimicrobial activity against various bacterial and fungal strains. Additionally, compounds were evaluated for the ability to inhibit Hepatitis C virus NS5B polymerase. The most active 4-thiazolidinone compound was 4k (SGK119) with 67.0 % and thiosemicarbazide compound was 5d (SGK123) with 69.50 % inhibition at 200 mu M against hepatitis C virus NS5B RNA polymerase. Anticancer activity of the selected compounds (3i, 3j, 3h, 4d, 4i and 6b) was determined at a single dose towards the full panel of 60 human cancer cell lines by the National Cancer Institute (NCI). 2-(2-Fluoro-4-biphenylyl)-N-[2-[4-(trifluoromethyl)phenyl]-4-oxo-1,3-thiazolidine-3-yl]propanamide 4d, containing thiazolidinone ring, demonstrated the most marked effect with 20.80 % growth percent on leukaemia cancer cell line SR at 10(-5) M. The results demonstrated that none of the compounds tested have anticandidal and antifungal activities, but two of them (4a and 4i) showed antibacterial inhibition against Micrococcus luteus, and Staphylococcus cohnii and Staphylococcus aureus, respectively.
Keywords: Anticancer activity; Hepatitis C NS5B polymerase; 4-Thiazolidinone; Hydrazide-hydrazone; Flurbiprofen; C VIRUS-INFECTION; NATIONAL-CANCER-INSTITUTE; TUMOR-CELL-LINES; HEPATITIS-C; HEPATOCELLULAR-CARCINOMA; R-FLURBIPROFEN; CYCLOOXYGENASE-2 EXPRESSION; POLYMERASE INHIBITORS; BIOLOGICAL-ACTIVITIES; ANTITUMOR-ACTIVITY